CONTEMPORARY APPROACHES TO THE FORMATION OF STUDENTS’ CIVIC COMPETENCE: INTERNATIONAL AND NATIONAL CONTEXTS - Anastasiia V. Tokarieva; Inna V. Сhyzhykova (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
The article is devoted to the analysis of youth civic education, civic engagement, and civic competence in international and national contexts. Over the last decades these themes have acquired importance in research, policy and practice in many parts of the world, including the EU and Ukraine. Citizenship, citizen, civic virtues, civic culture, civic competence are singled out by the authors as the key concepts of the discussed phenomena. Civic competence is defined as a path for a person to be included into a certain political or social community; it is the knowledge and exercising of the rights and duties of this community; it is a civic self-identification and a quality of a personality that necessitates his/her active participation in political or public life and characterizes his/her community involvement; it is a moral value that is based on the sense of patriotism, respect for human rights, sense of duty, responsibility, tolerance, solidarity. The genesis and the formation of the citizenship from the time of Aristotle to the present has passed the way from seeing it as a critical engagement with others; understanding and exercising one’s own rights and freedoms, and towards realizing the necessity of interdependence of the world nations and the world equality. The second part of the article substantiates the importance of youth civic education for both Ukraine and other countries as young people greatly influence the future of their nations. The main structural components of civic education that are presented by the authors include understanding key concepts, fostering respect for law, justice, democracy and common good, encouragement of thought independence. It develops skills of reflection, enquiry and debate. The article also presents the models of civic education for secondary and higher schools and highlights the problems related to the formation of civic education in Ukraine. The emphasis is placed on the use of serious video games as a promising tool for the formation of civic competence actively used in Western Europe. Examples of social projects based on serious video games, web platforms and mobile devices aimed at solving social problems of the society include Nutriciencia project, Ukrainian GameHub project, Hidden in the Part game. Conclusions are made about the need to recognize civic education not only as a subject of the curriculum, but as an integral part of educational policy – central to both educators and the society as a whole, both on the international and national levels.